Understanding the nature and dynamics of self-affirmation in non-depressed and subclinically depressed Indian adults: a thematic analysis - Gyanesh Kumar Tiwari; Priyanka Parihar; Ajit Kumar Singh; Amit Kumar Macorya; Anurag Shukla; Archana Singh; Archna Choudhary; Ashutosh Pandey (BMC Psychiatry)
Abstract Background Self-affirmation, a crucial concept that promotes self-esteem and individual development amidst life challenges, has proven therapeutic, preventative, and enhancing benefits. However, there is limited understanding regarding its frequency among individuals experiencing subclinical depression. This research aimed to understand the dynamics of self-affirmation, threats, and self-resources in both healthy (non-depressed) and subclinically depressed Indian adults. Methods Using a qualitative research design, forty-three individuals aged 20–30 years (18 healthy, 25 subclinically depressed individuals) were selected based on depression measurement. The data were collected through a semistructured interview. The interviews were audiotaped, transcribed verbatim and analysed using the thematic analysis method. Results Five themes were identified for subclinically depressed: social and relational threats, the tendency to magnify threats, negative cognitions and thoughts, denial/avoidance of threats, and poor awareness of self-resources. Five themes were also identified for healthy adults: explicit awareness of threats, common humanity, early responses to threats, adversity as an opportunity and easy availability of positive cognitions. Thus, the two groups differed significantly in their type, nature, and genesis of self-affirmation. For subclinically depressed, the major threats were related to health, financial conditions, employment, and relationships. These threats were positively and adaptively present in healthy adults. The subclinically depressed participants suffered from maladaptive tendencies and insufficient self-resources, while the healthy participants used positive self-resources and positive cognitions in dealing with the threats. Conclusions This study highlights the significant differences in self-affirmation processes between subclinically depressed and healthy adults. This finding supports the theoretical understanding that subclinical depression is associated with maladaptive cognitive patterns and a lack of self-resources. These findings underscore the importance of cognitive-behavioural frameworks that emphasize the role of positive self-affirmation and self-resources in mental health and highlight the need for targeted interventions that can strengthen these domains in subclinically depressed individuals. Therapeutic interventions for subclinical depression should focus on improving self-affirmation practices, increasing awareness of self-resources, and attenuating negative cognitive tendencies. Practitioners should consider integrating strategies that promote positive cognitions and proactive threat management. Additionally, preventative mental health programs could benefit from incorporating modules that strengthen self-affirmation and self-resource awareness of one’s resources to build resilience in the general population, particularly young adults.